Quantitative Estimation of I-123-Iomazenil Receptor Binding in Temporal Lobe Epilepsies Using Two SPECT Acquisitions – Comparison with the Regional Cerebral Blood Flow and a Compartment Model - Venz, S.; Hierholzer, J.; Cordes, M.; Straub, H. B.; Keske, U.; Meencke, H. J.; Eichstädt, H.; Felix, R. (Nuklearmedizin - NuclearMedicine, 1998)
Aim: To compare published fractional rate constants of I-123-lomazenil (IMZ) and C-11-Flumazenil (three-compartment/four-parameter model) with a I-123-lomazenil receptor index calculated from two SPECT acquisitions and to compare the receptor index of the epileptogenic area with the contralateral side in patients with unilateral temporal lobe epilepsies. Methods: 28 patients were studied. 13/28 patients had a drug-resistant unilateral temporal lobe epilepsy with a successful focus localisation performed by an extensive video/EEG monitoring. 15 other patients with clinically suspected focal epilepsy and a normal MRI and IMZ SPECT scanning were used as controls. SPECT scanning was performed in all patients 15 and 100 min after intravenous injection of 111 MBq IMZ and 10 min after application of 740 MBq Tc-99m-HMPAO. Quantification of the regional uptake was performed using ROI-technique and the specific and non-specific binding of IMZ was calculated. The receptor index was calculated by the difference of the specific binding from 15 to 100 min p. i. divided by the time interval. Results: The receptor index showed a linear correlation with recently published fractional rate constants k3 (r = 0.69 and 0.67; p = 0.15) and a moderate correlation with the k4 constant (-0.53 and -0.43; p = 0.28) by the means of C-11 -Flumazenil PET and 1-123-lomazenil SPECT studies, respectively. However, statistical significance was not reached due to the few data points available from the published reports. Furthermore, the IMZ receptor index was lower in the epileptogenic area of patients with unilateral temporal lobe epilepsies compared with their contralateral side (p = 0.02; Wilcoxon-test). The IMZ receptor index showed a weak correlation with the regional cerebral blood flow independent of the evaluated region (r <0.4; p <0.05). Conclusion: The IMZ receptor index indicated to be a simple routine approach to estimate the fractional rate constant k3 (r = 0.67). The lower value of the receptor index within the epileptogenic area might be due to a lower receptor density. However in further studies, IMZ might be a helpful tool to find out subtle changes of the receptor affinity due to its approximately 30-fold higher ligand-receptor affinity compared to C-11-Flumazenil.
Keywords: I-123-lomazenil; epilepsy; benzodiazepine receptor; compartment model analysis; single photon emission computed tomography